Teaching approaches of university professors in Mexico - Estévez Nenninger, Etty Haydee; Arreola Olivarría, Claudia Gabriela; Valdés Cuervo, Angel Alberto (Education Policy Analysis Archives, 2014)
This research aims to identify the extent to which university teacher’s work intersects with a cognitive-constructivist and comprehensive teaching approach and explore meaningful relationships between teaching approach expressed by the teacher and socio-demographic, academic and teaching career variables. A questionnaire was developed to measure the frequency of teaching activities specific to cognitive-constructivist instructional approach and comprehensive training (Estevez, 2002; Reigeluth, 1983, 1999). 250 teachers of the two major state universities of Sonora, Mexico were selected in a non-probabilistic way. The analysis of the results was performed using one-way ANOVAs testing and repeated measures, and post hoc Student t test for independent samples. It was concluded that the teachers surveyed developed a high frequency on educational planning activities with cognitive-constructivist approach and comprehensive training, however, an average level was showed in the definition of objectives and strategies related with teach to learn. Finally, it was found that the activities with cognitive constructivist orientation was higher in women, in teachers enrolled in a course assignment contract, which have more hours of teacher training and those who devote less time to research. This implies that the practice of activities of a cognitive-constructivist and comprehensive teaching approach is irregular and is affected by personal, academic and labor variables.